PENGARUH DANA PIHAK KETIGA, RETURN ON ASSET, DAN SUKU BUNGA KREDIT TERHADAP PENYALURAN KREDIT PADA BANK PERKREDITAN RAKYAT DI KOTA DENPASAR - Luh Eka Novianti; Sang Ayu Putu Arie Indraswarawati (UNHI Press, 2020)
The growth of bank lending in Indonesia has fluctuated every year. This is caused by several factors that affect lending. This study aims to determine the effect of DPK, ROA and credit interest rates on lending at BPR Denpasar. The population in this study is the BPR Bank, amounting to 13 companies. The sampling technique used was purposive sampling which is a type of sample selection with a specific purpose with the criteria that have been set and get 7 sample companies that are included with a period of 5 years. The data analysis technique used is multiple linear regression with the application of SPSS for windows. The results of the analysis show that DPK, ROA and credit interest rates together have a positive and significant effect on lending at BPR banks.